Characteristic Analysis of Torrefied Pellets: Determining Optimal Torrefaction Conditions for Agri-Byproduct - Sunyong Park; Seok Jun Kim; Kwang Cheol Oh; La Hoon Cho; Min Jun Kim; In Seon Jeong; Chung Geon Lee; Dae Hyun Kim (Energies, 2020)
This study considers the possibility of utilizing agri-byproducts as energy sources via pelletization and torrefaction. Pellets were placed in a capsule and torrefied in an electrical furnace. Subsequently, they were cooled for 30 min, and their mass loss was measured. To investigate the resulting changes in fuel characteristics, ultimate and proximate analyses were performed, and calorific values were measured. To estimate the water absorption of the pellets, hygroscopicity evaluations were conducted. Based on the experimental results, the energy yield, lower heating value, and exergy were calculated to determine the optimum conditions for torrefaction. The calculation was performed by utilizing the useful exergy and standards applied to biomass power plants. We determined that torrefaction for agro-pellets should be conducted under low-to-intermediate temperatures (210−250 °C) within a period of 50 min. Under these conditions, 7−55% mass reductions were observed, the higher heating value increased from 4110 to 6880 kcal kg−1, and the lower heating value changed from 3780 to 6520 kcal kg−1 owing to reduced hygroscopicity. So, Agro-byproducts can contribute to the practical application by improving the heating value through torrefaction as an alternative to wood pellets.